Bone morphogenetic protein‐2 expression in an intraductal papillary mucinous neoplasm with marked ossification: A case report. Issue 6 (8th May 2016) - Hadano, Atsuko; Hirabayashi, Kenichi; Yamamuro, Hiroshi; Takanashi, Yumi; Yamada, Misuzu; Kawanishi, Aya; Kawaguchi, Yoshiaki; Furukawa, Daisuke; Nakagohri, Toshio; Imai, Yutaka; Nakamura, Naoya; Mine, Tetsuya
Abstract : Intratumoral ossification has been reported in a number of epithelial tumors, but its presence in intraductal papillary mucinous neoplasms (IPMNs) is very rare. Herein, we present a rare case of IPMN with marked ossification. A 56‐year‐old Japanese man was under follow‐up for a previously diagnosed IPMN. Seven years later, he was found to have dilatation of the main pancreatic duct and an enlarged solid mass, for which pancreaticoduodenectomy was performed. Macroscopically, multiple and cystically dilated pancreatic branch ducts, as well as a dilated main pancreatic duct, were identified. There was a solid, polypoid hard mass measuring 15 × 12 mm in the cystically dilated branch of the duct in the pancreatic head. Histological examination revealed papillary proliferation of atypical cuboidal or columnar epithelial cells in the dilated main and branch pancreatic ducts. The solid mass included an invasive adenocarcinoma component with a tubular or trabecular structure that showed pronounced ossification. We diagnosed the patient with invasive IPMN accompanied by marked ossification. Immunohistochemically, tumor cells in both the non‐invasive and invasive lesions expressed bone morphogenetic protein‐2 (BMP‐2). While the mechanism of intratumoral ossification is unclear, it may have involved BMP‐2 in the present case.